Decompression and Fracturing Caused by Magmatically Induced Thermal Stresses. Issue 3 (17th March 2023) - Kiss, D.; Moulas, E.; Kaus, B. J. P.; Spang, A.
Abstract: Studies of host rock deformation around magmatic intrusions usually focus on the development of stresses directly related to the intrusion process. This is done either by considering an inflating region that represents the intruding body, or by considering multiphase deformation. Thermal processes, especially volume changes caused by thermal expansion are typically ignored. We show that thermal stresses around upper crustal magma bodies are likely to be significant and sufficient to create an extensive fracture network around the magma body by brittle yielding. At the same time, cooling induces decompression within the intrusion, which can promote the appearance of a volatile phase. Volatile phases and the development of a fracture network around the inclusion may thus be the processes that control magmatic‐hydrothermal alteration around intrusions. This suggests that thermal stresses likely play an important role in the development of magmatic systems. To quantify the magnitude of thermal stresses around cooling intrusions, we present a fully compressible 2D visco‐elasto‐plastic thermo‐mechanical numerical model. We utilize a finite difference staggered grid discretization and a graphics processing unit based pseudo‐transient solver. First, we present purely thermo‐elastic solutions, then we include the effects of viscous relaxation and plastic yielding. The dominant deformation mechanism in our models is determined in a self‐consistent manner, by taking into account stress, pressure, and temperature conditions. Using experimentally determined flow laws, the resulting thermal stresses can be comparable to or even exceed the confining pressure. This suggests that thermal stresses alone could result in the development of a fracture network around magmatic bodies. Plain Language Summary: Quantifying the stresses that magma bodies exert on the surrounding rocks is an important part of understanding mechanical processes that control the evolution of magmatic systems and volcanic eruptions. Previous analytical or numerical models typically describe the mechanical response to changes in magma volume due to intrusion or extraction of magma. However, volume changes related to thermal expansion/contraction around a cooling magma body are often neglected. Here, we develop a new software which runs on modern graphics processing unit machines, to quantity the effect of this process. The results show that stresses due to thermal expansion/contraction are significant, and often large enough to fracture the rocks nearby the magma body. Such fracture networks may form permeable pathways for the magma or for fluids such as water and CO2, thus influencing the evolution of magmatic and hydrothermal systems. Finally we show that cooling and shrinking of magma bodies causes significant decompression which can influence the chemical evolution of the magma during crystallization and devolatilization. Key Points: We present a numerical quantification of the effect of thermal stresses in visco‐elasto‐plastic rock with tensile and dilatant shear failure The pressure drop in thermally contracting upper crustal magma bodies can exceed 100 MPa, potentially triggering devolatilization Thermal cracking can create an extensive fracture network around an upper crustal magma body